Analisis Penggunaan Media Sosial Sebagai Edukasi Parenting Pada Kalangan Orang Tua Muda di Desa Grantung Kab. Purbalingga - Gilang Karenina Fiqiah; Mu’arifudin Mu’arifudin (Journal on Education, 2024)
This research aims to describe the motives for using social media as parenting education, the types of social media used, parenting techniques applied through the use of social media, the impact of social media as parenting education for young parents in Grantung Village. This research uses a qualitative approach with descriptive methods. Data collection techniques using interviews, observation and documentation. Data analysis methods are data collection, data reduction, data presentation, and drawing conclusions. The research results showed that the motives that encourage young parents are information motives, personal identity motives, social interaction motives and entertainment. Meanwhile, the types of social media that are popularly used by young parents include YouTube, Instagram, WhatsApp and also TikTok. The parenting techniques that are applied are discipline techniques, monitoring techniques, reward techniques, daily routines and prearming. positive and negative impacts. The positive impact felt is the ease of interacting, getting information, saving time, and expanding relationships. Meanwhile, the negative impact felt is the occurrence of differences of opinion with fellow parents or also with previous people, the spread of hoax information, and errors in theory.